A review of Scandinavian writing research between 2010 and 2020. (2nd July 2022) - Bremholm, Jesper; Kabel, Kristine; Liberg, Caroline; Skar, Gustaf B
Abstract : Scandinavian writing research forms a relatively new field, with an increased number of studies conducted in the last two decades. In this qualitative synthesis review of 87 peer reviewed journal articles from Denmark, Norway, and Sweden published between 2010 and 2020, the aim was to outline the landscape of current educational writing research from the region. The sample included research articles published in both Scandinavian and international journals. Our analysis focused on the articles' research approaches and main themes regarding the object of investigation. The main themes identified were Writing Instruction, Writing Assessment, and Students' Text. We found a predominance of studies conducted in the context of language arts/first language (L1) education, concerning either disciplinary or general aspects of writing. We also found a predominance of approaches based on either sociocultural or social semiotic theory. Furthermore, a majority of the reviewed studies were explorative and small-scale, and, for the Writing Assessment studies in particular, directed at the secondary stages of school. The results suggest a call for future studies focusing on writing interventions and studies deploying a wide range of methodological approaches, as well as studies based on inter-Scandinavian collaborations across Denmark, Norway, and Sweden.